Case reportLeft atrial appendage closure in secondary prevention of stroke in a patient with atrial fibrillation as well as prior stroke and iatrogenic intracranial haemorrhage - Lasek-Bal, Anetta; Puz, Przemysław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
We present a case of a female patient after a transient ischaemic attack (TIA) and a brain infarction, in addition to other risk factors for stroke including atrial fibrillation, in whom warfarin was used for secondary prevention. Three months after a brain infarction, the patient experienced bleeding in the left hemisphere of the brain that was most likely a complication of anticoagulant therapy. Given the restrictions in the choice of stroke prevention methods, and the limitations associated with the patient’s negativism, we decided to use an alternative method for secondary prevention of cerebral ischaemia, namely percutaneous closure of the left atrial appendage (LAA). The procedure and post-procedure course were uneventful. During an 8-month follow-up, the patient did not experience new cerebrovascular accidents.